A Customized Social Network Platform (Kids Helpline Circles) for Delivering Group Counseling to Young People Experiencing Family Discord That Impacts Their Well-Being: Exploratory Study - Campbell, Andrew; Ridout, Brad; Amon, Krestina; Navarro, Pablo; Collyer, Brian; Dalgleish, John (JMIR Publications, 2019)
BackgroundIt has often been reported that young people are at high risk of mental health concerns, more so than at any other time in development over their life span. The situational factors that young people report as impacting their well-being are not addressed as often: specifically, family discord. Kids Helpline, a national service in Australia that provides free counseling online and by telephone to young people in distress, report that family discord and well-being issues are one of the major concerns reported by clients. In order to meet the preferences that young people seek when accessing counseling support, Kids Helpline has designed and trialed a custom-built social network platform for group counseling of young people experiencing family discord that impacts their well-being. ObjectiveIn this exploratory study, we communicate the findings of Phase 1 of an innovative study in user and online counselor experience. This will lead to an iterative design for a world-first, purpose-built social network that will do the following: (1) increase reach and quality of service by utilizing a digital tool of preference for youth to receive peer-to-peer and counselor-to-peer support in a safe online environment and (2) provide the evidence base to document the best practice for online group counseling in a social network environment. MethodsThe study utilized a participatory action research design. Young people aged 13-25 years (N=105) with mild-to-moderate depression or anxiety (not high risk) who contacted Kids Helpline were asked if they would like to trial the social networking site (SNS) for peer-to-peer and counselor-to-peer group support. Subjects were grouped into age cohorts of no more than one year above or below their reported age and assigned to groups of no more than 36 participants, in order to create a community of familiarity around age and problems experienced. Each group entered into an 8-week group counseling support program guided by counselors making regular posts and providing topic-specific content for psychoeducation and discussion. Counselors provided a weekly log of events to researchers; at 2-week intervals, subjects provided qualitative and quantitative feedback through open-ended questions and specific psychometric measures. ResultsQualitative results provided evidence of user support and benefits of the online group counseling environment. Counselors also reported benefits of the modality of therapy delivery. Psychometric scales did not report significance in changes of mood or affect. Counselors and users suggested improvements to the platform to increase user engagement. ConclusionsPhase 1 provided proof of concept for this mode of online counseling delivery. Users and counselors saw value in the model and innovation of the service. Phase 2 will address platform issues with changes to a new social network platform. Phase 2 will focus more broadly on mental health concerns raised by users and permit inclusion of a clinical population of young people experiencing depression and anxiety. Trial RegistrationAustralian New Zealand Clinical Trials Registry (ANZCTR) ACTRN12616000518460; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=370381